An integrative review: Developing and measuring creativity in nursing. (March 2018) - Ma, Xing; Yang, Yuanyuan; Wang, Xue; Zang, Yuli
Abstract: Objective: To analyze and synthesise the existing evidence on creativity in nursing. Design: An integrative review. Data Sources: A systematic search was conducted using seven English databases (PubMed, Science Direct, Web of Science, Cochrane, EBSCO, Wiley, and Medline) and the top three best Chinese databases (CNKI, Wanfang Data, and VIP). Review Methods: The combined keywords, creativity and nursing/nurse, were used to search for relevant journal articles that were written in English or Chinese from January 1995 to December 2016. The components of articles, i.e. title, abstract, full-text and the cited reference, were screened, filtered, evaluated and recorded according to the PRISMA statements and Joanna Briggs Institute Checklists. Thematic analysis was performed to synthesise evidence from the full-texts of studies. Results: Fifteen quantitative and seven qualitative studies were included in this review. A joyful affective perspective enriched the conceptualization of creativity in nursing. Many intrinsic factors (e.g. learning styles, thinking styles, intrinsic passion, interest in nursing and achievement motivation) or extrinsic factors (mostly workplace problems and nurses' shortage) could influence nurses' and nursing students' creativity. Artistic expressions (e.g. painting, music, and pottery), self-directed learning and group/team work were reported to have a positive effect on creativity enhancement. None of existing instruments can adequately measure nurses' or nursing students' creativity. Conclusions: The concept of creativity requires an explicit definition, which is essential to the development and evaluation of creativity in nursing education and practice. Many factors influencing nurses' and nursing students' creativity can be implemented to achieve positive outcomes through efforts at artistic expressions, self-directed learning and teamwork. An instrument with satisfactory psychometric properties should be available for monitoring creativity development among nurses and nursing students. Highlights: A joyful affective aspect enriches the conceptualization of creativity in nursing. Intrinsic and extrinsic factors influence nurses' and nursing students' creativity. Artistic expressions, self-directed learning and group/team work have positive effects on creativity improvement. It is vital to develop an instrument with satisfactory psychometric properties to measure the creativity in nursing.